Indonesian Scientific Writing by Using Communicative Approach - . Sobri (Bandar Lampung University (UBL), 2014)
The aim of writing this article is to describe communicative approach in learning Indonesian scientific writing. This article consist of implementing Indonesian scientific writing by using communicative approach. The method used in this research is research and development. The technique used in collecting the data are observation, interview, theoretical foundation, and teaching in the class and out of the class. The data analysis technique used consist of two approaches, qualitative and quantitative approach. The result effectiveness test shows that means of class that uses communicative approach is 66, meanwhile class that uses conventional approach is 54. The students activity of model class is more than 91% are active and high motivation in learning, meanwhile the non model class the students activity less than 70%. Based on the data, it can be concluded that implementing of the communicative approach in learning Indonesian scientific writing are able to improve the students’ process and learning achievement of Indonesian scientific writing.